PROJECT-BASED LEARNING IN ISLAMIC CULTURAL HISTORY LESSONS THROUGH CREATING DOCUMENTARY VIDEOS: CHALLENGES AND BENEFITS ACCORDING TO STUDENTS - Muttaqin, Mohammad Izdiyan; Dardiri, Ahmad; Fajarini, Ulfah (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study aims to reveal the learning process based on documentary video projects in the subject of Islamic Cultural History and students' opinions about the learning process. The research was conducted during the pandemic when online learning was implemented at MAN 4 Jakarta. This is a qualitative descriptive study, data was collected through observation, answers from an open-ended question questionnaire from 27 students, and interviews with 2 students. The results of this study indicate that the documentary video-based learning process can be carried out through three main stages: preparation, execution, and assignment collection. Each of these stages has details of their respective activities. The students revealed that the difficulties they faced were the problem of managing time, as well as difficulties in recording narration and editing. The benefits that students feel include that they feel that this video-based learning trains them to communicate, to work together, to be more independent and more creative. The students also felt that they gained new skills in the learning process, such as the skills of editing videos and uploading them on social media. Some students suggested that the video project continue with some improvements, and others wanted an easier assignment. The researcher concludes that documentary video project-based learning has many benefits and is one of the alternative learning models that can be chosen to provide variety in learning process and to develop the 21st century skills.